Business Risk and Sales Growth as Determinants of Capital Structure - Carolina, Cyntia; Surya, Tiara Lilis; Maryanto, Maryanto (The Future of Education Journal, 2026)
This study focuses on a single research object, namely PT Mayora Indah, Tbk. The purpose of this study is to examine: (1) the partial effect of business risk on capital structure at PT Mayora Indah, Tbk; (2) the partial effect of sales growth on capital structure at PT Mayora Indah, Tbk; (3) the simultaneous effect of business risk and sales growth on capital structure at PT Mayora Indah, Tbk; and (4) the magnitude of the influence of business risk and sales growth on the capital structure of PT Mayora Indah, Tbk. The research methodology employed a descriptive qualitative and descriptive quantitative approach. The results of the study indicate that: (1) partially, business risk has no significant effect on the capital structure of PT Mayora Indah, Tbk during the period 2012–2021, as evidenced by the value of –t_calculated > –t_table (–0.156 > –2.30600); (2) partially, sales growth has no significant effect on the capital structure of PT Mayora Indah, Tbk during the period 2012–2021, as indicated by the value of –t_calculated > –t_table (–1.081 > –2.30600); (3) simultaneously, business risk and sales growth have no significant effect on the capital structure of PT Mayora Indah, Tbk during the period 2012–2021, as shown by the value of F_calculated < F_table (0.585 < 4.74); and (4) the magnitude of the influence of business risk and sales growth on the capital structure of PT Mayora Indah, Tbk is 12.8%.